2009
DOI: 10.22495/cocv7i2p6
|View full text |Cite
|
Sign up to set email alerts
|

Managerial ownership, capital structure and firm value

Abstract: This paper extends prior research to examine the managerial ownership influences on firm performance through the choices of capital structures by using a new sample of S&P 500 firm in 2005. The empirical results of OLS regressions replicate the nonlinear relationship between managerial ownership and firm value. However, we found that the turning points had moved up in our sample compared with previous papers, which implies that the managerial control for pursuing self-interest, and the alignment of interests b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
73
3
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 67 publications
11
73
3
10
Order By: Relevance
“…Peningkatan jumlah hutang merupakan sinyal positif bagi investor. Ruan et al (2011) menunjukkan bahwa struktur modal perusahaan (leverage) berpengaruh terhadap nilai perusahaan karena pengawasan dari kreditor lebih ketat untuk memastikan perusahaan memaksimalkan kinerjanya. Dengan demikian, penelitian ini berhipotesis bahwa: H5 : Solvabilitas berpengaruh positif terhadap Nilai Perusahaan…”
Section: Pengaruh Solvabilitas Terhadap Nilai Perusahaanunclassified
“…Peningkatan jumlah hutang merupakan sinyal positif bagi investor. Ruan et al (2011) menunjukkan bahwa struktur modal perusahaan (leverage) berpengaruh terhadap nilai perusahaan karena pengawasan dari kreditor lebih ketat untuk memastikan perusahaan memaksimalkan kinerjanya. Dengan demikian, penelitian ini berhipotesis bahwa: H5 : Solvabilitas berpengaruh positif terhadap Nilai Perusahaan…”
Section: Pengaruh Solvabilitas Terhadap Nilai Perusahaanunclassified
“…At the empirical study, the results are mitigated, but they converge on the finding of a non-linear relationship between two variables such as inverted U-shaped as the work of (McConnell and Servaes (1990), Hu and Zhou (2008) and Chen et al (2012)) or cubic type (N Form) such as studies by (Short and Keasey (1999), Ruan et al (2011) and Cheng et al (2012)) or quadratic relation as the study of (Cui and Mak (2002) and McConnell and Servaes (1990)) or quantum relation such as the study of (Davies et al(2005), .…”
Section: Managerial Ownership / Performancementioning
confidence: 96%
“…We adapt a model of piecewise linear regression to highlight the effect of non-linearity of the managerial ownership, in accordance with the same approach in the studies of Morck et al (1988), Hess et al (2010), Ruan et al (2011) andCheng et al (2012). More precisely, the managerial ownership variable (.manag prop) is divided as follows:…”
Section: Managerial Ownership / Performance / Board Of Directorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruan et al (2011) found an unlinier relationship between ownership and the firm value and capital structure.…”
Section: Introductionmentioning
confidence: 99%